(3GdehLR aj GdWHs - (3GdbQTj, GHf GdfajS, YdGA GdOjf, Ydj Hf CHj GdMRe, J(B687 (3g`s
(3ChdgG (B:s
(3HSe Gddg bGd GdTjN GdGeGe bO QJHJ gPG GdcJGH Ydi CQHYI afhf Gdaf GdChd aj bhGYO LRFj GdWH CYfj YdejI hYedjI Hbhd cdj ; Gdaf GdKGfj aj GdCOhjI hGdCZPjI s
(3BNQgG (B:s
(3hGdMei GdHdZejI Jchf MQGQGJgG bdjdI dG JdPZ GdjO EdG EPG GWjdJ WhjdG hJfhH cd jhe hJCNP Ch TQGH hQhG hTQGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\270s
(3cTa GdXfhf (B2\1899s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs